A concepção de religiosidade na obra de Viktor Emil Frankl - Corrêa, Diogo Arnaldo (2013)
The objective of this study was to understand the concept of religiousness in the work of Viktor Emil Frankl. Were described his biography and his work and conducted a thematic analysis from fourteen of his books chosen due to their correlation with the purpose of the research. Frankl's ideas were investigated in chronological course of their work, and possible extensions in regard to the subject were averaged and displayed through five topics "God", "Faith", "Religion", "Religiousness" and "Psychotherapy and Religiosity." Finally, spelled out the understandings reached and final considerations. Frankl believes humans broadly, total single, integrated. His anthropological perspective cooperates directly to a performance that includes psychotherapy patients beyond reductionism and consider their existential possibilities. Such possibilities unfold through the capabilities of self-transcendence, consciousness, freedom and responsibility, and aid in discovery of the meaning of life by conducting creative values, experiential and attitudinal. Among such existential possibilities of the human being appreciated for Logotherapy, religiosity can be considered as a potential that arises spontaneously and is also configured from religious and cultural contexts. For Frankl, psychotherapy can legitimately occupy the religious because it relates to the deepest dimension of the human being and the positions he takes over the world and that it is when there is a free choice and responsible attitudes marked by intuition of his consciousness, which sets religiosity as one of the possibilities for gift of life sense. Therefore, the therapist must help the patient accept and considering it in its entirety and conserving open to receive their experiences, including those that are marked by religiosity, the natural and personal relationships with the sacred, linked to its inherent search for meaning, can derive the discovery of meaning to their existence and to promote their quality of life